Komparasi Desain Alat Penukar Panas Tipe Air-Cooled - Ikhsan Kamil, Muhammad; Agustina Sari, Dessy (Jurnal Teknologi, 2023)
The discussion regarding detailed comparisons of air-cooled heat exchanger designs using mathematical equation calculations was carried out based on several literature sources related to heat exchanger design using simulation model calculations in the Aspen EDR V10 software.. This ACHE-type heat exchanger is designed to carry out processes with hot fluid in the form of saturated water vapor at a pressure of 2 bar and cold fluid in the form of air at a pressure of 1,101 bar. The saturated water vapor used has a temperature of 251,2oF, and the air used has a temperature of 84,2oF. The variables used for comparison are the performance parameters of the heat exchanger, which include the log mean temperature difference, pressure drop (ΔP), fouling factor (RD), heat transfer rate (Q), and overall heat transfer coefficient (U). The calculation results show that the mathematical model calculations and the simulation model in the software have differences, but that does not change the fact that the two calculation models produce tool performance parameter values that are in accordance with operating standards when viewed from the pressure drop value, fouling factor value, and heat transfer coefficient value. Overall, if you look at the type of fluid used in the process,